An analytical study of some determinants of demand for insurance in the Libyan market (Economic studies journal, 2020)
This study aimed primarily to identify some of the determinants of demand for insurance in the Libyan insurance market, in addition to identifying the type and extent of the relationship that links these determinants with insurance demand in the Libyan market, and to study the impact of the financial income variable, the level of insurance awareness, and urbanization. , on insurance demand, and to provide a scientific contribution by finding and revealing the determinants of insurance demand, identifying the most important factors affecting the growth of the insurance industry in the Libyan insurance market, and presenting some proposals and recommendations that can benefit decision-makers in the Libyan insurance market, and in order to complete these The study used the descriptive and analytical approach and some statistical methods to study the reality of the insurance sector in Libya and to prove or deny the study hypotheses through the (SPSS) Social Science for Package Statistical program with the aim of arriving at valuable connotations and indicators that support the subject of the study, after collecting data and published periodic reports. About the study population consisting of insurance companies operating in the Libyan insurance market, and one of the most important findings of the study from the data analysis results is that there are several determinants that lead to the weakening of the insurance sector in the Libyan insurance market, and that there is a moral effect between some of the determinants of demand for insurance and the insurance sector In the Libyan market, including that there is a direct relationship between income and demand for insurance, and between urbanization and insurance demand. The study suggested some recommendations, the most prominent of which are improving the performance of insurance companies in the Libyan insurance market through increasing advertising and media campaigns, and improving income in general for members of society. With attention to the urbanization factor and the geographical distribution of companies